Maturation of White Adipose Tissue Function in C57BL/6j Mice From Weaning to Young Adulthood - Kodde, Andrea; Engels, Eefje; Oosting, Annemarie; van Limpt, Kees; van der Beek, Eline M.; Keijer, Jaap (Frontiers in Physiology, 2019)
White adipose tissue (WAT) distribution and WAT mitochondrial function contribute to total body metabolic health throughout life, but little is known about maturation of WAT function following weaning. We therefore assessed changes in mitochondrial density and function markers in WAT depots of young mice. Inguinal (ING), epididymal (EPI) and retroperitoneal (RP) WAT of 21, 42 and 98 days old C57BL/6j mice was collected. Mitochondrial density (citrate synthase (CS), mtDNA) and function (subunits of oxidative phosphorylation complexes (OXPHOS)) markers were analyzed, together with gene expression of browning markers (Ucp1, Cidea). mRNA of ING WAT of 21 and 98 old mice was sequenced to further investigate functional changes of the mitochondria and alterations in cell populations. CS levels decreased significantly over time in all depots. ING showed most pronounced changes, including significantly decreased levels of OXPHOS complex I, II and III subunits and gene expression of Ucp1 (PN21-42 and PN42-98) and Cidea (PN42-98). White adipocyte markers were higher at PN98 in ING WAT. Analyses of RNA sequence data showed that the mitochondrial functional profile changed over time from ‘growth-supporting’ mitochondria focused on ATP production (and dissipation), to more steady-state mitochondria with more diverse functions and higher biosynthesis. Mitochondrial density and energy metabolism markers declined in all three depots over time after weaning. This was most pronounced in ING WAT and associated with reduced browning markers, increased whitening and an altered metabolism. In particular the PN21-42 period may provide a time window to study mitochondrial adaptation and effects of nutritional exposures relevant for later life metabolic health.